Engel Curves in Medellin’s Households 2012-2015 (2019)
This paper analyzes and characterizes the consumer behavior and the consumption patterns in Medellin’s households. We made the analysis based on the Engel curves for urban households, which relates the total expenditure to expenditure in specific goods. We perform three empirical models: semiparametric models to capture non-linearities, instrumental variables model because of the endogeneity and Tobit models due to censoring of the dependent variable. We concluded that food and beverage, tobacco and clothing and footwear, respond to the Engel Law, and depending on the expenditure segment in which the families are located, those goods could be normal, inferior or luxury.